A cost-effective strategy for enhancing mobility in aging communities: the case of Narita City - Ojima, Takuto; Hiekata, Kazuo; Nakashima, Takuya (Frontiers in Sustainability, 2025)
In depopulated areas with aging populations, it is challenging to design public transportation services. This is because municipalities are expected to provide mobility to as many people as possible within a limited budget while considering the various modes of transportation in that municipality. This study therefore aims to explore sustainable transport policies that will improve both the mobility aspect for older adults and the financial aspect for municipalities. Specifically, we take Narita City, Chiba Prefecture, as an example, which operates demand-responsive transport (DRT) services and where urban and rural areas coexist. We then developed various transport policy scenarios, for example, varying the degree to which demand-responsive transport is operated, or adding a subsidy system through taxi ticket distribution, and comparing them on two axes: the municipality cost and the mobility indicator QoM (Quality of Mobility). By using QoM, we can evaluate changes in individual mobility and quantitatively analyze how transportation inconvenience and the impact of policy changes vary depending on individual attributes even within the same municipality. The results indicated that improving DRT convenience or introducing taxi subsidies led to increased costs to some extent but also significantly enhanced mobility levels. In particular, the more difficult it was for people to travel, the higher the impact– highlighting the importance of DRT for these individuals. Furthermore, we found that there were significant differences in mobility among residents depending on their residential area. This study suggests the need for a comprehensive approach that addresses not only public transportation but also urban planning to bridge these gaps.